2016
DOI: 10.4209/aaqr.2016.11.0472
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and Outdoor Concentrations of Polybrominated Diphenyl Ethers on Respirable Particulate in Central and Southern Taiwan

Abstract: High levels of fine particulate (PM 2.5 ) in indoor and outdoor air have globally threatened human health and environment. There are still few studies which concern on the emerging persistent organic pollutants like polybrominated diphenyl ethers (PBDEs) bound on PM 2.5 . The aim of this study was to investigate PBDEs in PM 2.5 in various outdoor (metropolis, industrial, and rural areas) and indoor (library, rail station, hospital, supermarket, department store, and office) environments. PM 2.5 -bound PBDEs wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
18
1
1
Order By: Relevance
“…Badania prowadzone w róż-nych budynkach użytku publicznego (m.in. szkoły, uczelnie, przedszkola, biura, biblioteki) potwierdziły, że przy braku wewnętrznych źródeł stężenia drobnego PM w powietrzu wewnętrznym są zbliżone od tego w powietrzu atmosferycznym albo od niego wyższe (Worobiec i in., 2010;Zwoździak i in., 2013;Alves i in., 2014;Mainka i in., 2015;Błaszczyk i in., 2016;Chao i in., 2016;Oliviera i in., 2016). Czło-wiek największą część swojego życia przebywa w pomieszczeniach.…”
Section: Wprowadzenieunclassified
“…Badania prowadzone w róż-nych budynkach użytku publicznego (m.in. szkoły, uczelnie, przedszkola, biura, biblioteki) potwierdziły, że przy braku wewnętrznych źródeł stężenia drobnego PM w powietrzu wewnętrznym są zbliżone od tego w powietrzu atmosferycznym albo od niego wyższe (Worobiec i in., 2010;Zwoździak i in., 2013;Alves i in., 2014;Mainka i in., 2015;Błaszczyk i in., 2016;Chao i in., 2016;Oliviera i in., 2016). Czło-wiek największą część swojego życia przebywa w pomieszczeniach.…”
Section: Wprowadzenieunclassified
“…Thus, the infant's health is extremely susceptible to the air pollutant, PM 2.5 , and it can be considered as a toxic precursor to the impairment of a child's neurodevelopment. PM 2.5 -bound persistent organic pollutants (POPs) such as organochlorine pesticides (OCPs), polybrominated diphenyl ethers (PBDEs), and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) were reported in previous studies (Chao et al, 2016;Chen et al, 2018b;Zhao et al, 2018). The high organic matter content of PM 2.5 as compared to coarse PMs can be attributed to a higher POPs sorption (Odabasi et al, 2015).…”
Section: Introductionmentioning
confidence: 91%
“…Ni et al (2011) indicated that human exposure to PM 2.5 -bound PBDEs might have a minor contribution to total non-dietary PBDE exposure. In terms of global scientific reports, few studies have considered PM 2.5 -bound PBDE levels in the indoor environment (Beser et al, 2014;Li et al, 2015a;Xu et al, 2015;Chao et al, 2016;Deng et al, 2016). To our knowledge, there are no known reports that have investigated the levels of PM 2.5 -bound DP, NBFRs, or PBDD/Fs in the indoor environment.…”
Section: Future Work For Hfrs and Pbdd/fs In The Indoor Environmentmentioning
confidence: 99%
“…Numerous studies have turned their focus on PM 2.5 levels due to the possibility of these small particles being deposited deep into the lungs, thus causing respiratory ailments and diseases, as well as other negative health problems (Zhang et al, 2013;Gautam et al, 2016;Hwang et al, 2016;Lee et al, 2016;Lu et al, 2016;Xing et al, 2016;Ma et al, 2017). People with a known history of cardiopulmonary problems face Ma et al, 2009Suzuki et al, 2010Suzuki et al, 2010Tue et al, 2010Tue et al, 2010Tue et al, 2013Remberger et al, 2014Remberger et al, 2014Remberger et al, 2014Gou et al, 2016Gou et al, 2016Gou et al, 2016Gou et al, 2016 CALUX assay with the unit of pg = CALUX-TEQ g Hsu et al, Aerosol and Air Quality Research, 18: 2047-20632059 higher risk of mortality due to the increasing PM 2.5 concentrations in the atmosphere while normal people also face a higher risk of developing respiratory problems (Dominici et al, 2006;de Oliveira et al, 2012;Xing et al, 2016;Li et al, 2017)…”
Section: Future Work For Hfrs and Pbdd/fs In The Indoor Environmentmentioning
confidence: 99%
See 1 more Smart Citation